3-[3-(2-Fluorobenzoyl)thioureido]propionic acid - Ngah, Nurziana; Mohamed, Nor Azanita; Mohd Yamin, Bohari; Mohd Zaki, Hamizah (International Union of Crystallography, 2014)
In the title compound, C10H11FN3O3S, the 2-fluorobenzoyl and proponic acid groups maintain a trans–cis conformation with respect to the thiono C ￼ ￼ S bond across their C—N bonds. The propionic acid group adopts an anti conformation about the C—C bond, with an N—C—C—C torsion angle of 173.8 (2)